Critical thinking gone sinking? the curious case of Azizan Osman / Norzie Diana Baharum - Baharum, Norzie Diana (2016)
With the advent of a millennial invention called social networking, humans' ability to think critically has been tested many a time. Controversial issues surrounding the society spread fast via this networking, enabling greater number of people to involve in hotly debated discussions. This interestingly leads to many divided opinions - those of the supporters, opponents and neutrals - the virtual war of words with no or little solid information presented to justify their personal views and preferences. This is when the art of critical thinking is lost in the social networking discussions, where critical thinking elements like clarity, accuracy, relevance, logic and precision among many others are usually faded in the presence of emotional outburst, ignorance and fanaticism, consequently leaving a room for weak and fallacious arguments. This paper argues on the disappearance of critical thinking standards in a Facebook post, comments and replies on the recent academic fraud allegedly done by a renowned entrepreneur and motivator, Azizan Osman. Logical fallacies evident in the thread were grouped and tabulated and frequency counts were recorded. Findings show that critical thinking standards were mostly absent in this type of discourse with the fallacy of Red Herring being firstly committed which later led to Ad Hominem! Personal Attack fallacy being mostly used by the commenters.